(untitled) (Balneo and PRM Research Journal, 2024)
Injuries to the vertebral artery (VA) may be traumatic or spontaneous. Traumatic injuries are most frequently due to blunt spinal cord injury (SCI) or may be due to penetrating trauma. Upper cervical spine fractures and accompanying subluxation, as well as transverse process fractures extending into the artery bone foramen, are associated with an elevated risk of VAI. Clinical case. A 63-year-old female patient with flaccid C4 AIS quadriplegia (global motor score 3/100), vertebral myelopathy, neurogenic bladder, sacral pressure sore, and blindness was transferred from the Spinal Neurosurgical Department. The patient fell from the same level and suffered a minor brain concussion and cervical spinal cord injury (SCI) on October 1, 2022, followed by a C6 vertebral body fracture and a C5-6 dislocation, operated on October 7, 2022 (anterior spinal cord decompression with dislocation reduction and mixed anterior fusion with bone graft and fixation screws). She complained of blindness and partial optic atrophy in both eyes that progressively occurred after the traumatic event due to a stroke in the bilateral territory of the posterior cerebral artery (PCA), secondary to bilateral VAI. Imagery confirmed the diagnosis and the outcomes: bilateral occipital stroke and a subacute/chronic lacunar lesion in the right thalamus.